Canine decidualization in vitro: extracellular matrix modification, progesterone mediated effects and selective blocking of prostaglandin E2 receptors - Felix R. GRAUBNER; Miguel TAVARES PEREIRA; Alois BOOS; Mariusz P. KOWALEWSKI (The Society for Reproduction and Development, 2020)
Recently, we established an in vitro model with immortalized dog uterine stromal (DUS) cells for investigations into canine-specific decidualization. Their capability to decidualize was assessed with cAMP and prostaglandin (PG) E2. Here, we show that the effects of PGE2 are mediated through both of the cAMP-mediating PGE2 receptors (PTGER2/4). Their functional inhibition suppressed gene expression of PRLR and PGR in DUS cells. We also assessed the effects of cAMP and PGE2 on selected extracellular matrix components and CX43, and showed that cAMP, but not PGE2, increases COL4, extracellular matrix protein 1 (ECM1) and CX43 protein levels during in vitro decidualization, indicating a mesenchymal-epithelial decidual transformation in these cells. Thus, although PGE2 is involved in decidualization, it does not appear to regulate extracellular matrix. Further, the role of progesterone (P4) during in vitro decidualization was addressed. P4 upregulated PRLR and PGR in DUS cells, but these effects were not influenced by PGE2; both P4 and PGE2 hormones appeared to act independently. P4 did not affect IGF1 expression, which was upregulated by PGE2, however, it suppressed expression of IGF2, also in the presence of PGE2. Similarly, P4 did not affect PGE2 synthase (PTGES), but in the presence of PGE2 it increased PTGER2 levels and, regardless of the presence of PGE2, suppressed expression of PTGER4. Our results indicate a reciprocal regulatory loop between PGE2 and P4 during canine in vitro decidualization: whereas P4 may be involved in regulating PGE2-mediated decidualization by regulating the availability of its receptors, PGE2 regulates PGR levels in a manner dependent on PTGER2 and -4.